Posture, muscle activity and oxygen consumption evaluations among metal stamping operators: A pilot study in Malaysian small and medium industries - Isa, Halim; Abdul Rahman, Omar, Ir. Prof. Dr. Hj.; Ahmad Rasdan, Ismail, Ir. (The Institution of Engineers, Malaysia (IEM), 2012)
Link to publisher's homepage at http://www.myiem.org.my/